FITUR-FITUR SEMANTIK NOMINA DALAM SYAIR GULUNG KETAPANG KARYA MAHMUD MURSALIN - Likhani, Mifthakhul; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe and classify the results of the analysis of the types of   nouns and semantic features of nouns in Syair Gulung by Mahmud Mursalin. As well as preparing e-modules using the scrolled poetry as a learning medium. This research uses a descriptive method in the form of qualitative research. This research uses a semantic approach. The data source in this research is Syair Gulung by Mahmud Mursalin. This research data is in the form of an analysis of the types of nouns and the semantic features of nouns in the form of understanding the nouns contained in the rolled poetry. The data collection technique uses documentary study techniques with the researcher himself as a data collection tool. The results of this research show that there are 92 data which are types of nominations in Syair Gulung by Mahmud Mursalin. Of the 92 data, it is divided into 14 noun categories, namely 25 data of person nouns, 6 data of animal nouns, 3 data of plant nouns, 5 data of fruit nouns, 9 data of time nouns, 2 data of place nouns, 7 data of material nouns, 2 equipment noun data, 5 food noun data, 31 personal noun data, 50 general noun data, 42 special noun data, 85 concrete noun data, and 7 abstract noun data. The implementation of Indonesian language learning used in this research is in the form of an E-Module for Folk Poetry for Class VII, Even Semester, Middle School level, 2013 Curriculum.